Heterodyne Optical Time Domain Reflectometer Combined With Active Loss Compensation: A Practical Tool for Investigating Fermi Pasta Ulam Recurrence Process and Breathers Dynamics in Optical Fibers - Naveau, Corentin; Vanderhaegen, Guillaume; Szriftgiser, Pascal; Martinelli, Gilbert; Droques, Maxime; Kudlinski, Alexandre; Conforti, Matteo; Trillo, Stefano; Akhmediev, Nail; Mussot, Arnaud (Frontiers in Physics, 2021)
We report recent results obtained with a novel optical fiber experimental setup based on a heterodyne optical time-domain reflectometer in the context of FPU recurrence process. Moreover, we actively compensate the dissipation of the system. We show that we can observe several FPU recurrences by monitoring the power and relative phase evolutions of the main discrete frequency components involved in the process.